2022
DOI: 10.3389/fmed.2022.842991
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of Myalgic Encephalomyelitis/Chronic Fatigue Syndrome With Partial Least Squares Discriminant Analysis: Relevance of Blood Extracellular Vesicles

Abstract: Myalgic Encephalomyelitis/Chronic Fatigue Syndrome (ME/CFS), a chronic disease characterized by long-lasting persistent debilitating widespread fatigue and post-exertional malaise, remains diagnosed by clinical criteria. Our group and others have identified differentially expressed miRNA profiles in the blood of patients. However, their diagnostic power individually or in combinations seems limited. A Partial Least Squares-Discriminant Analysis (PLS-DA) model initially based on 817 variables: two demographic, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…[ 423–427 ]), including rheumatoid arthritis [ 428–433 ]. In particular, extracellular vesicles are seen as a highly discriminating accompaniment to ME/CFS [ 434 ], and are being observed in both acute [ 435 ] and Long COVID-19 [ 436 ] patients.…”
Section: Size Of Fibrin Amyloid Microclots and Capillary Diametersmentioning
confidence: 99%
“…[ 423–427 ]), including rheumatoid arthritis [ 428–433 ]. In particular, extracellular vesicles are seen as a highly discriminating accompaniment to ME/CFS [ 434 ], and are being observed in both acute [ 435 ] and Long COVID-19 [ 436 ] patients.…”
Section: Size Of Fibrin Amyloid Microclots and Capillary Diametersmentioning
confidence: 99%
“…These peaks are proposed to reflect erythrocyte deficiencies in ME/CFS patients. 230 Xu et al analyzed single peripheral blood mononuclear cells using Raman microspectroscopy and identified Raman bands associated with phenylalanine are significantly higher in ME/CFS patients than in healthy controls. The difference is related to mitochondrial/energetic dysfunctions.…”
Section: Red Blood Cell Deformabilitymentioning
confidence: 99%
“…The carotenoid peaks are highlighted as the main difference between severe ME/CFS patients and healthy controls. These peaks are proposed to reflect erythrocyte deficiencies in ME/CFS patients 230 . Xu et al.…”
Section: Perspectives: Where We Are Looking and Where We Might Lookmentioning
confidence: 99%
“…The study identified specific Raman peaks that correlated with ME/CFS phenotypes, offering potential insights into biological changes and supporting the development of new therapeutics. Another study of blood-diagnosis of ME/CFS achieved perfect classification by analzing a collective set of data including demographic, blood analytic, PBMC miRNAs, extracellular vesicle (EV) miRNAs, and EV feature for 15 severe ME/CFS females and 15 healthy subjects [ 54 ].…”
Section: Raman Micro-spectroscopy Unveiled: Illuminating Metabolism A...mentioning
confidence: 99%